2016
DOI: 10.1021/acs.jnatprod.5b01142
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Isoprenoid-Derived Natural Products from a Dongsha Atoll Soft Coral Sinularia erecta

Abstract: Four new isoprenoids, including two norcembranoids sinulerectols A and B (1 and 2), a cembranoid sinulerectol C (3), and a degraded cembranoid sinulerectadione (4), along with three known isoprenoids, an unnamed norcembrene (5), sinularectin (6), and ineleganolide (7), and a known nitrogen-containing compound (Z)-N-[2-(4-hydroxyphenyl)ethyl]-3-methyldodec-2-enamide (8), were isolated from an extract of the marine soft coral Sinularia erecta. The structure of sinularectin (6) was revised, too. Compounds 3, 4, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…As in previously described procedures, the assay of superoxide anion generation was conducted according to the SOD-inhibitable reduction of ferricytochrome C. The elastase release experiment was performed using MeO–Suc–Ala–Ala–Pro–Val– p -nitroanilide as the enzyme substrate [23]. Idelalisib, a selective inhibitor of phosphatidylinositol-3-kinase, was used as a positive control for inhibition of superoxide anion generation and elastase release with IC 50 0.07 ± 0.01 and 0.3 ± 0.1 μM [24]. …”
Section: Methodsmentioning
confidence: 99%
“…As in previously described procedures, the assay of superoxide anion generation was conducted according to the SOD-inhibitable reduction of ferricytochrome C. The elastase release experiment was performed using MeO–Suc–Ala–Ala–Pro–Val– p -nitroanilide as the enzyme substrate [23]. Idelalisib, a selective inhibitor of phosphatidylinositol-3-kinase, was used as a positive control for inhibition of superoxide anion generation and elastase release with IC 50 0.07 ± 0.01 and 0.3 ± 0.1 μM [24]. …”
Section: Methodsmentioning
confidence: 99%
“…In 2016, Huang et al ., reported a 11‐hydroperoxy‐cembranoid, sinulerectol C ( 49 ) (Figure ), obtained from S. erecta , collected off the coast of Dohgsha Atoll, Taiwan . The structure of cembranoid 49 was elucidated by spectroscopic methods, and this compound was found to exhibit cytotoxicity towards the K‐562 tumor cells, with an IC 50 value of 9.2 μM …”
Section: Alcyonaceamentioning
confidence: 99%
“…Many cembrane-based natural products have been shown to exhibit significant activities such as cytotoxicity [1,2,3,4,5,6,7,8,9,10,11,12,13,14] and anti-inflammatory activity [9,11,13,14,15,16,17,18]. From the experience of searching bioactive metabolites from soft corals, series of cembranoids have been unveiled from octocorals (Alcyonaceae) belonging to the genera Sarcophyton , [1,2,3,4,5,6,7,8,16], Sinularia [9,10,11,12,17,18] and Lobophyton [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…From the experience of searching bioactive metabolites from soft corals, series of cembranoids have been unveiled from octocorals (Alcyonaceae) belonging to the genera Sarcophyton , [1,2,3,4,5,6,7,8,16], Sinularia [9,10,11,12,17,18] and Lobophyton [13,14,15]. Also, previous studies showed that two cembranoid units could form biscembranoid-type compounds by Diels-Alder reaction [19,20,21], radical dimerization [22,23], or connection with a sulfur atom [18], making the chemistry of cembranes more complex and interesting than monomeric form.…”
Section: Introductionmentioning
confidence: 99%